Efficacy Of Plant Solvents Extracts Against Xanthomonas Axonopodis Pv. Citri Causing Citrus Canker (Journal of Plant Disease Sciences, 2022)
In vitro antibacterial properties of some solvents, such as petroleum ether, chloroform, ethyl acetate, dichloromethane, distilled water, and methanol extraction of two plants, Azadirachta indica and Eucalyptus globulus, were studied against Xanthomonas axonopodis pv. citri, the primary agent of citrus canker disease. Azadirachta indica whole plant extract had the highest extraction yield (9.08%) in distilled water and the lowest (2.9%) in petroleum ether, whereas Eucalyptus globulus extract had the highest extraction yield (9.01%) in methanol and the lowest (7.01%) in ethyl acetate solvent. By agar well diffusion and paper disc method, chloroform extract of Azadirachta indica and methanol extract of Eucalyptus globulus were found to have promising antibacterial action against Xanthomonas axanopodis pv. citri. The chloroform leaf extract of Azadirachta indica showed the maximum percentage of inhibition when compared to the methanol extract of Eucalyptus globulus.
Keywords: Citrus canker; In vitro; Plant extract; X. axonopodis pv. citri